The significance Of pilgrimage (Hajj) in a muslim’s religious and social life - Yousif, Ahmad (Institut Kefahaman Islam Malaysia, 2012)

(untitled)
The acts of worship constitute the five pillars or cornerstones of Islam, each of which has its own spiritual and social values. One who believes in these pillars enters the fold of Islam and becomes a member of the Muslim community (the ummah). It is these ceremonial obligations that draw the faithful closer to God and help them fulfill their duty to Him. The purpose of Islamic worship is, therefore, to strengthen the individual’s faith and sense of submission to Allah, and to reinforce the ties of brother and sisterhood among Muslims. In order to examine the significance of Hajj to Mecca in a Muslim’s social and spiritual life, this analysis on the subject will be introduced.